Mineros y militares en la coyuntura actual de Bolivia, Chile y Perú (1976-1978) - Zapata, Francisco (Revista Mexicana de Sociología, 2024)
Mineros y militares en la coyuntura actual de Bolivia, Chile y Perú (1976-1978).